AN ANALYSIS OF PROJECT-BASED LEARNING IN DEVELOPING ARGUMENTATIVE WRITING SKILLS IN ENGLISH LANGUAGE TEACHING AT SMAN 2 KOTA PAYAKUMBUH - Ahmad Abdillah; Robi Kurniawan (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2026)
This study aimed to analyze the implementation of the Project‑Based Learning (PjBL) model in teaching argumentative writing in English and to explore students’ perceptions of its effectiveness at SMAN 2 Kota Payakumbuh. This research employed a descriptive quantitative approach. The population consisted of 432 eleventh-grade students, from which Class XI F5 (36 students) was selected as the sample using purposive sampling. Data were collected through structured observation (field notes) and a 20‑item Likert-scale questionnaire and were analyzed using descriptive statistics. The observation results indicated that the teacher successfully implemented the six essential stages of PjBL systematically, including formulating essential questions, designing the project, developing a schedule, monitoring project progress, assessing outcomes, and evaluating learning experiences, while fully meeting all ten operational indicators. Meanwhile, the questionnaire results revealed that students held very positive perceptions of PjBL in developing their argumentative writing skills, with an overall mean score of 3.25 out of 4.00 (81.25%). The category Teacher Support and Monitoring received the highest rating (mean = 3.35), indicating that students greatly valued active guidance and constructive feedback from the teacher throughout the project. Students also reported that PjBL increased their learning motivation and helped them organize logical arguments effectively in analytical exposition texts. Based on these findings, it is recommended that English teachers integrate PjBL as an alternative method for teaching writing, while future researchers are encouraged to conduct experimental studies to measure the quantitative effectiveness of PjBL on a larger population.